2021
DOI: 10.1177/0956462420980641
|View full text |Cite
|
Sign up to set email alerts
|

Delayed diagnosis of lymphogranuloma venereum in a hospital setting – a retrospective observational study

Abstract: Objective: The incidence of lymphogranuloma venereum (LGV) in Europe is increasing. However, diagnosing LGV in a hospital setting is rare. We analysed the diagnostic process and clinical characteristics of patients with LGV in a hospital setting. Design and setting: A retrospective observational study conducted in a teaching hospital in Amsterdam, The Netherlands. All adult patients with LGV between November 2010 and February 2019 were included. Clinical data were retrieved from electronic patient records. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…A study showed that among those with a confirmed NG or CT visit, balanitis was observed in 24% of cases and genital warts in 12% of cases ( 25 ). Lymphogranuloma venereum (LGV) is caused by CT, and 22.5% of infections had symptoms of inguinal lymph node enlargement ( 26 ). Therefore, it would be useful to link these symptoms with NG and CT when offering symptomatic management.…”
Section: Discussionmentioning
confidence: 99%
“…A study showed that among those with a confirmed NG or CT visit, balanitis was observed in 24% of cases and genital warts in 12% of cases ( 25 ). Lymphogranuloma venereum (LGV) is caused by CT, and 22.5% of infections had symptoms of inguinal lymph node enlargement ( 26 ). Therefore, it would be useful to link these symptoms with NG and CT when offering symptomatic management.…”
Section: Discussionmentioning
confidence: 99%